Translating DPYD genotype into DPD phenotype: using the DPYD gene activity score. (July 2015) - Henricks, Linda M; Lunenburg, Carin ATC; Meulendijks, Didier; Gelderblom, Hans; Cats, Annemieke; Swen, Jesse J; Schellens, Jan HM; Guchelaar, Henk-Jan
The dihydropyrimidine dehydrogenase enzyme (DPD, encoded by the gene DPYD ) plays a key role in the metabolism of fluoropyrimidines. DPD deficiency occurs in 4–5% of the population and is associated with severe fluoropyrimidine-related toxicity. Several SNPs in DPYD have been described that lead to absent or reduced enzyme activity, including DPYD*2A, DPYD*13, c.2846A>T and c.1236G>A/haplotype B3. Since these SNPs differ in their effect on DPD enzyme activity, a differentiated dose adaption is recommended. We propose the gene activity score for translating DPYD genotype into phenotype, accounting for differences in functionality of SNPs. This method can be used to standardize individualized fluoropyrimidine dose adjustments, resulting in optimal safety and effectiveness.